Graphic devices and the early decorated book - Brown, Michelle (Michelle P.); Garipzanov, Ildar H.; Tilghman, Benjamin C. (Boydell studies in medieval art and architecture., 2017)
In our electronic age, we are accustomed to the use of icons, symbols, graphs, charts, diagrams and visualisations as part of the vocabulary of communication. But this rich ecosystem is far from a modern phenomenon. Early medieval manuscripts demonstrate that their makers and readers achieved very sophisticated levels of "graphicacy". When considered from this perspective, many elements familiar to students of manuscript decoration - embellished characters in scripts, decorated initials, monograms, graphic symbols, assembly marks, diagrammatic structures, frames, symbolic ornaments, musical notation - are revealed to be not minor, incidental marks but crucial elements within the larger sign systems of manuscripts. This interdisciplinary volume is the first to discuss the conflation of text and image with a specific focus on the appearance of various graphic devices in manuscript culture. By looking at their many forms as they appear from the fourth century to their full maturity in the long ninth century, its contributors demonstrate the importance of these symbols to understanding medieval culture. Michelle P. Brown FSA is Professor Emerita of Medieval Book History at the School of Advanced Study, University of London and was formerly the Curator of Illuminated Manuscripts at the British Library; Ildar Garipzanov is Professor of Early Medieval History at the Department of Archaeology, Conservation and History at the University of Oslo; Benjamin C. Tilghman is Assistant Professor of Art History at Washington College. Contributors: Tina Bawden, Michelle P. Brown, Leslie Brubaker, David Ganz, Ildar H. Garipzanov, Cynthia Hahn, Catherine E. Karkov, Herbert L. Kessler, Beatrice Kitzinger, Kallirroe Linardou, Lawrence Nees, Eric Palazzo, Benjamin C. Tilghman.